ANALISIS PREFERENSI KONSUMEN DALAM MEMBELI MINYAK GORENG - Larasati, Dyah Siti Ayu; Putri, Elvika Nungki Chintia; Kusuma, Bela; Anitasari, Silvia; meilina, Restin (Universitas Nusantara PGRI Kediri, 2022)
Abstract As one of the nine urgently needed, consumption of cooking oil increased from year to year. In 2021 the demand for cooking oil in Indonesia was higher than the supply, resulting in a fairly high price increase. The government is trying to anticipate this by setting HET but instead it creates a shortage of products so that this policy is revoked except for bulk cooking oil. This makes cooking oil producers prefer to sell their products in packaging so that the selling price is higher. As a result, consumers face the choice of having to queue for hours to get bulk cooking oil or spend more money to buy packaged cooking oil whose price is quite large. The purpose of this study is to answer the problem formulation (1) How do packaging, price, size, clarity, color, nutritional information, promotion, brand, and accessibility become the basis for consumers to buy cooking oil? (2) How can the order of packaging, price, size, clarity, color, nutritional information, promotion, brand, and accessibility become the basis for consumers to buy cooking oil? (3) What is the most dominant attribute in buying cooking oil? and (4) Based on the attributes of packaging, price, size, clarity, color, nutritional information, promotion, brand, and accessibility, consumers are more dominant in choosing bulk or packaged cooking oil. The method used is descriptive qualitative through in-depth interviews with 3 informants. The results show that price is the most dominant attribute in buying cooking oil preferences. The order of these attributes is different for each informant, but the most dominant attribute is the same price. Based on the analysis of each attribute, consumer preference is higher for bulk cooking oil because the price is cheaper.